Contrast‐enhanced sonography of thyroid nodules. Issue 3 (18th October 2014) - Jiang, Jue; Huang, Lili; Zhang, Hongli; Ma, Wenqi; Shang, Xue; Zhou, Qi; Gao, Ya; Yu, Shanshan; Qi, Yanhua
ABSTRACT Purpose To investigate the value of contrast‐enhanced ultrasound (CEUS) in the differentiation of benign and malignant nodules. Methods One hundred eighty‐nine patients with 213 thyroid nodules were enrolled in this retrospective study. All patients underwent preoperative CEUS and were subsequently scheduled for surgery. The pathology results were obtained after surgery. The time‐intensity curves were plotted with TomTec software. The quantitative parameters of the time‐intensity curve, such as the maximum intensity of peak (IMAX), the rise time from 10% to 90% of the IMAX, and the time to peak, were compared between the benign and malignant nodules. Results There were no significant differences in the rise time or the time to peak among thyroid papillary carcinoma, nodular goiter, and follicular adenoma. However, a significant difference was identified in the IMAX. Conclusions A quantitative evaluation of CEUS is helpful to differentiate benign and malignant thyroid nodules. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:153–156, 2015;